Grundtvig og Billeder - Thomsen, Niels (Grundtvig-studier, 2001)
Grundtvig and Images By Niels Thomsen What statements Grundtvig makes about art - pictures, sculpture, poetry - are cautious or even negative. It appears clearly from his great poem I Know o f a Land from 1824 with its disassociation from the art conception of Romanticism and its belief that eternity could be grasped in art. It is further elaborated in some letters to the Romantic poet Ingemann in 1837-38, in which Grundtvig may well appreciate art as the trace of the spirit, but emphasizes that where the trace of the spirit is mistaken for the spirit itself, it will lead to idolatry of art and to inane barbarism.Grundtvig’s guarded attitude to pictorial art may seem surprising since few poets have been so visually gifted as he was, as it is shown in a number of his hymns and songs: O Christendom, Ancestral Land by the Billowing Shore, If Your Hand You Have Put to the Plough o f the Lord.Many of the images in Grundtvig’s poems bear such a resemblance to pictures and mosaics from Antiquity and medieval times that it might be supposed that Grundtvig was familiar with them, but he was not. It is a much more likely explanation that Grundtvig sees in the same way as pictorial artists do. Grundtvig himself theorizes in several places about his use of imagery which he explains on the basis of his view of the Hebrew language with its abundance of imagery as the basic language, but it is argued in the present article that it is of equal importance that fundamentally Grundtvig thinks and perceives in images. His theological perception is clarified through the images he sees before him. The images seem to offer themselves to him before the rational understanding, a form of perception that he shares with the Semitic Apocalyptics of the first centuries.It is one thing that Grundtvig has not met with the spirit in art. It is quite another that pictorial artists have been abundantly inspired by Grundtvig’s imagery. This is demonstrated in Joakim Skovgaard’s and Sven Havsteen-Mikkelsen’s pictorial interpretation of The Blessed Day we See with Joy. But the rich imagery of precisely that hymn demonstrates at the same time how impossible it is to exhaust, in physical pictures, the visions seen by Grundtvig. This must be seen in the context of Grundtvig’s understanding of the corporal and the incorporeal. Faith needs images in order that Christianity may not turn into a figment of the brain, but if one believes that the spirit can be captured in physical pictures, one is on the way to idolatry.